Incorporação de fibras curtas de bambu (Bambusa vulgaris) e resíduo industrial de caulim em compósitos de matriz polimérica: resistência à tração e fractografia - BARBOSA, Karla Suellen Lino (2018)
Currently the composite materials have gained prominence in their manufacture and industrial application. Researchers have shown interest in this area of materials due to their sustainable development. Plant fibers and industrial wastes that have often inadequate disposal have been widely sought by researchers as cargoes for these composite materials. In this work, composite materials of Iso - polical Polyester matrix with insertion of bamboo plant fibers in the lengths of 15 and 30 mm were produced, composites with industrial residue load of kaolin flint with 100 mesh granulometry and hybrid residues / fiber composites. The composites were made according to the hand lay-up method. For each series, 6 (six) specimens were produced. The polymer matrix showed proportions of: catalyst 1 % and accelerator 1,5 %. The fiber fractions were 10, 20, 30 and 40%, and the hybrid composites had values of: 3% fiber / 10% Residue, fiber 3% / residue 20% and fiber 3% / residue 30%. Traction tests of the composites were performed according to ASTM D-3039 and fracture surface analyzes by scanning electron microscopy (SEM). The results showed that there was an increase in the tensile strength limit of the composites in relation to the full matrix. The best resistance limit results were: 41.89 MPa and 27.06 MPa for 15 and 30 mm bamboo fibers, respectively, both with a 1% fiber content; 31.44 MPa for residue kaolin flint; 24.47 MPa for hybrid composites 20% kaolin residue flint + 3% bamboo fibers 15 mm and 33.75 MPa for hybrid composites 20% kaolin residue flint + 3% bamboo fibers 30 mm. The morphological analyzes of the fracture surfaces were efficient for the determination of the fault mechanisms and characteristics present in the materials, where the phenomena of fibers arranged transversely in the direction of loading and ruptured fibers were the most observed mechanisms.